Empowering Religious Educators in the Digital Age: An Evaluation of an ICT-Based Media Training Program - M. Imamul Muttaqin Arsandhi; Bahrul Ulum; Mufaizin Mufaizin; Junaidi Junaidi (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2025)
This study evaluates a training program designed to enhance the competence of religious educators, known as "penyuluh agama" in Indonesia, in utilizing ICT-based media for religious education. The program, conducted in Bangkalan Regency, aimed to equip participants with the knowledge and skills to develop and manage effective religious education media in the digital age. A needs assessment was conducted to inform the curriculum development, which covered fundamental aspects of ICT, introduction to ICT-based media, technical skills, and effective communication strategies. The training employed interactive workshops and provided ongoing support to participants. Evaluation results indicated significant improvement in participants' understanding and utilization of ICT-based media for religious education, as well as fostering a strong sense of community among them. This study highlights the effectiveness of ICT-based media training in empowering religious educators to adapt to the evolving needs of the community and expand the reach of religious education in the digital age.